IMPACT OF LOSS AVERSION TO THE MARKET IN THE PHILIPPINES - Samontina, Mary Christine; Campos, Karl (Kusa Lawa, 2025)
Loss aversion, a cognitive bias where people weigh potential losses more heavily than equivalent gains, has been extensively studied in behavioral economics (Liu, 2023). This review will explore the factors that condition loss aversion in decision-making: age, education, experience, and cultural norms. All these influences further shape the way people respond to financial decisions, although typically the more experienced or older the person is, the more level-headed he will be in his response to loss. Cultural and social influences play a huge part, especially in the way that societal values can either augment or dampen loss. Marketers have led such consumer behavior over the years by using loss aversion to develop odd-even pricing, product bundling and time-limited offers that attract attention through a false sense of urgency or value for selling more and maximizing profits. The paper promotes rationalistic choice for consumers arguing that increased awareness about loss aversion increases the understanding and balancing features in the choice process. It would occur by increasing the level of financial literacy and understanding of the psychological drivers behind people's decisions, ensuring consumers would avoid impulsive decisions in marketing tactics. The review relied more on the reality of loss aversion in the degree of consumer behavior and marketing. Keywords: loss aversion, cognitive biases, behavioral economics, consumer decision-making